P227 Efficacy And Safety Of Budesonide–formoterol (bf) Spiromax® In Adults And Adolescents With Asthma: Randomised Comparison With Bf Turbuhaler®. (10th November 2014) - Virchow, JC; Gopalan, G; Rodriguez-Roisin, R; Shu, Y
Abstract : Background: DuoResp Spiromax ® (Teva Pharmaceuticals) is a dry-powder inhaler designed to deliver budesonide and formoterol fumarate (BF Spiromax ® ) with maximum ease of use. Pharmacokinetic studies have shown bioequivalence of BF Turbuhaler ® . This study compared the efficacy and safety of these devices in patients with asthma. Methods: This was a 12-week, multicentre, double-blind, randomised, controlled trial (N=605). Eligible patients (≥12 years old) had persistent asthma with FEV1 40–85% predicted, had used a SABA and ICS for ≥8 weeks before screening and were maintained on stable-dose ICS for 4 weeks. The primary objective was to demonstrate non-inferiority of twice-daily BF Spiromax ® 160/4.5mcg to BF Turbuhaler ® 200/6mcg, with respect to change from baseline in weekly average of daily trough morning PEF. Results: This analysis was based on the per protocol population (N=290 and N=284 for BF Spiromax ® and BF Turbuhaler ® groups, respectively). The least squares mean change from baseline to Week 12 in morning PEF was 18.8 L/min with BF Spiromax ® and 21.796 L/min with BF Turbuhaler ® . Non-inferiority of BF Spiromax ® vs BF Turbuhaler ® was demonstrated, as the lower limit of the 95% two-sided CI (–9.02 L/min) is greater than –15 L/min. Similarly, no significant between-group differences were observed in secondary efficacy endpoints. Both devices were well tolerated, with no significant differences in the incidence of adverse events or asthma exacerbations. Conclusions: This study has demonstrated the non-inferiority of BF Spiromax ® vs BF Turbuhaler ® in adults and adolescents with asthma. Further data are required to confirm whether BF Spiromax ® can be used as an alternative to BF Turbuhaler ® in other indications. Sponsor: Teva Pharmaceuticals.